2020
DOI: 10.1007/s40313-020-00665-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Starter Alternator PMSM Drive for Hybrid Vehicles

Abstract: Transportation electrification is gaining notoriety in recent years as to fulfill the aim of reducing the fossil fuels consumption and to increase energy efficiency. Accordingly, integrated starter alternator is a compelling method to convert conventional vehicles into hybrid ones. A deal of benefits can be reached by using ISA systems. In general, it provides vehicles performance enhancement and also reduces fuel consumption. This paper aims to present simulation results and preliminary experimental achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Nowadays, the environmental and economical concerns are major motives for developing electric vehicles (EVs), especially with the rapid increase in pollution, the world recognizes the urgency to look for sustainable mobility solutions for the purpose of reducing dependency on imported energy sources (Song et al 2018). Research has shown that EVs have the best advantage for the environment, they emit less greenhouse gases and air pollution over their life than petrol or diesel vehicles (Zhang et al 2020;Babaeia et al 2020;Godoy et al 2021;Iannuzzi and Franzese 2020). According to actual research, there are a few disadvantages of owning an electric vehicle including, the battery recharging takes time, this challenge can be overcome in the future by developing new batteries with novel adapters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, the environmental and economical concerns are major motives for developing electric vehicles (EVs), especially with the rapid increase in pollution, the world recognizes the urgency to look for sustainable mobility solutions for the purpose of reducing dependency on imported energy sources (Song et al 2018). Research has shown that EVs have the best advantage for the environment, they emit less greenhouse gases and air pollution over their life than petrol or diesel vehicles (Zhang et al 2020;Babaeia et al 2020;Godoy et al 2021;Iannuzzi and Franzese 2020). According to actual research, there are a few disadvantages of owning an electric vehicle including, the battery recharging takes time, this challenge can be overcome in the future by developing new batteries with novel adapters.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, this problem can be bypassed, when many other manufacturers begin producing electric vehicles massively. EVs have a shorter range than gas-powered vehicles, this challenge can be resolved in the future by developing a new battery technologies with the B Aziz El Janati El Idrissi ajanatiidrissi@uae.ac.ma 1 LTI Laboratory, ENSAT, Abdelmalek Essaadi University, Tetouan, Morocco objective of storing energy and more intelligent algorithms to manage it (Godoy et al 2021;Iannuzzi and Franzese 2020). In contrast, electric vehicles are more eco-friendly than petrol and diesel vehicles, they do not emit toxic gases in the environment as they run on electrically powered engines, which is a clean energy source that contribute to a healthy and green climate (Song et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation